The Impact of Kadatua Dialect on Students' English Pronunciation - Suryadi, Ray; Al Hakim, Rohima Nur Aziza; Hamid Basri, La Ode Muhammad Idrus; Reskiawan, Bimas (Lingual Journal of Language and Culture; Vol 15 No 1 (2023): Lingual: Journal of Language and Culture, 2023)
This paper presents descriptive quantitative research investigating how the Kadatua dialect can influence the English pronunciation of second-grade students of SMPN 1 Maginti. The subjects of this study were 8 second-grade students at SMPN 1 Maginti with Kadatua ethnic background. The research instrument used was an interview and a test. The test was done by asking students to read a list of several English words to record and analyse their pronunciation. The results show that Kadatua dialect influenced students’ pronunciation of the following sounds: /?/, /æ/, /??/, /??/, /a?/, /??/, /e?/, /??/, /ð/, /?/, and /?/. Although some sounds cannot be pronounced correctly, it does not mean they are affected because these sounds do not exist in the Kadatua dialect alone. This would mean that the Kadatua dialect does not affect the overall students' English pronunciation. Some of the sounds that are not influenced by the Kadatua dialect are as follow: /?/, /?/, /i?/, /u?/, /??/, /??/ /e/, /e?/, /a?/, /??/, /p/, /b/, /t/, /d/, /k/, /g/, /t?/,/d?/, /f/, /s/, /z/, /?/, /h/, /m/, /n/, /?/, /l/, /r/, /j/, and /w/. Although these sounds can be pronounced properly and correctly, it does not mean that all these sounds are only found in the Kadatua dialect. This ease of pronunciation is identified because of the dialect features similarity of Kadatua with English language.